2014
DOI: 10.1007/s11060-014-1592-1
|View full text |Cite
|
Sign up to set email alerts
|

Leptomeningeal dissemination in glioblastoma; an inspection of risk factors, treatment, and outcomes at a single institution

Abstract: There are few studies reporting the incidence of leptomeningeal dissemination (LMD) in patients with glioblastoma; only small case series have been published. Consequently, there are no established standards of care for these patients. Therefore, we undertook this retrospective review to evaluate a large series of patients with glioblastoma treated at MD Anderson Cancer Center to estimate the incidence of LMD and assess the impact of a variety of treatment modalities. Analysis was performed on 595 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(124 citation statements)
references
References 19 publications
6
117
1
Order By: Relevance
“…In the present study, ventricular opening during surgery was not correlated with leptomeningeal dissemination at recurrence or poor survival, consistent with previous reports [15,19,20]. Our results suggested that surgical difficulty based on close proximity to subcortical fibers and critical neurological tissue, as well as surgical intervention including ventricular opening along with tumor involvement of the SVZ, were less likely to contribute to poor survival than the biological nature of tumor cells and the anatomical environment of the SVZ.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, ventricular opening during surgery was not correlated with leptomeningeal dissemination at recurrence or poor survival, consistent with previous reports [15,19,20]. Our results suggested that surgical difficulty based on close proximity to subcortical fibers and critical neurological tissue, as well as surgical intervention including ventricular opening along with tumor involvement of the SVZ, were less likely to contribute to poor survival than the biological nature of tumor cells and the anatomical environment of the SVZ.…”
Section: Discussionsupporting
confidence: 91%
“…glioblastoma) evidence of LM is not rare: Autopsy series suggest an incidence of approximately 20-25% [11,12]. A symptomatic dissemination is reported only in about 2% [13] and an overall diagnosis made by imaging or positive cerebrosinal fluid cytology in about 4% of patients [14,15]. However, breast cancer (27-50%), lung cancer (22-36%) and melanoma (12%) account for most cases in large series of this disorder [16].…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…However, for recurrent patients, re-radiation was always not recommended due to the dose restriction. In addition, this study did not focus on one chemotherapy regimen and fail to provide an effective therapeutic approach [17]. Most of the other published studies were case reports [18][19][20].…”
Section: Promising Results Of This Rh-es-combined Chemotherapymentioning
confidence: 99%